2016
DOI: 10.1167/iovs.16-19593
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Zebrafish Mfrp Causes Nanophthalmia, Hyperopia, and Accumulation of Subretinal Macrophages

Abstract: PurposeMutations in membrane frizzled-related protein (MFRP) are associated with nanophthalmia, hyperopia, foveoschisis, irregular patches of RPE atrophy, and optic disc drusen in humans. Mouse mfrp mutants show retinal degeneration but no change in eye size or refractive state. The goal of this work was to generate zebrafish mutants to investigate the loss of Mfrp on eye size and refractive state, and to characterize other phenotypes observed.MethodsClustered regularly interspaced short palindromic repeats (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…Complex cases with retinal involvement (RP features or ERG changes) were found in 6/19 (31.6%) of the families with a molecular diagnosis, mostly due to MFRP mutations (5/6, 83.3%). The retinal involvement in the MFRP-associated group is in line with previous phenotypic studies 39 and is in agreement with its expression pattern in human, mouse and zebrafish eyes www.nature.com/scientificreports www.nature.com/scientificreports/ including neural and pigmentary retina 3,20,21 and its role in photoreceptor outer segment maintenance 50 . An additional explanation could be the fact that MFRP and a gene implicated in late-onset retinal dystrophy, C1QTNF5 (encoding C1q and tumor necrosis factor related protein 5) are both expressed as a bicistronic transcript and found to co-localize to the same tissues with a clear functional relationship in the retina 51,52 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Complex cases with retinal involvement (RP features or ERG changes) were found in 6/19 (31.6%) of the families with a molecular diagnosis, mostly due to MFRP mutations (5/6, 83.3%). The retinal involvement in the MFRP-associated group is in line with previous phenotypic studies 39 and is in agreement with its expression pattern in human, mouse and zebrafish eyes www.nature.com/scientificreports www.nature.com/scientificreports/ including neural and pigmentary retina 3,20,21 and its role in photoreceptor outer segment maintenance 50 . An additional explanation could be the fact that MFRP and a gene implicated in late-onset retinal dystrophy, C1QTNF5 (encoding C1q and tumor necrosis factor related protein 5) are both expressed as a bicistronic transcript and found to co-localize to the same tissues with a clear functional relationship in the retina 51,52 .…”
Section: Discussionsupporting
confidence: 88%
“…The presence of papillomacular folds was found to be more frequent in MCOP (12/19, 63.2%) than in NNO (3/6, 50%). It has been proposed that these papillomacular folds result from the disparity between the retinal and scleral growth which seems to be more prominent in MCOP cases, although no clear genotype-phenotype correlations have been established yet 16,21,48 .…”
Section: Discussionmentioning
confidence: 99%
“…To develop an RPE injury model, we utilized a transgenic line in which an rpe65a promoter element drives expression of the nfsB-EGFP fusion protein in mature RPE (34) (rpe65a:nfsB-GFP; SI Appendix Fig S1A,B). nfsB is an E. coli nitroreductase that converts the prodrug metronidazole (MTZ) into a potent DNA crosslinking agent, leading to apoptosis in expressing cells (35,36).…”
Section: Rpe Ablation Results In Amd-like Phenotypesmentioning
confidence: 99%
“…Interestingly, exon 5 appears to be a hotspot for MFRP mutations of various types (nonsense, frameshift and missense, as well as splice acceptor site variants). Recently, Collery et al (Collery et al 2016) showed that loss of mfrp causes nanophthalmia and hyperopia in zebrafish models.…”
Section: Mfrp (Membrane Frizzled-related Protein)mentioning
confidence: 99%